Engagement of immune effector cells by trastuzumab induces HER2/ERBB2 downregulation in cancer cells through STAT1 activation - Shi, Yun (BioMed Central, 2014)
INTRODUCTION: Trastuzumab has been widely used for the treatment of human epidermal growth factor receptor 2 (HER2) overexpressing breast cancer for more than a decade. However, reports on the involvement of HER2 downregulation in trastuzumab’s mechanism of action are inconsistent. The aim of this study is to investigate if the dependence of trastuzumab-mediated cancer cell HER2 downregulation on immune effector cells represents a novel mechanism of action for trastuzumab. METHODS: HER2 expression was evaluated by Western blotting, flow cytometry, and real-time polymerase chain reaction (PCR) in cell lysates from co-cultures of multiple cancer cell lines with peripheral blood mononuclear cells (PBMCs) in the presence or absence of trastuzumab. The engagement of immune cells by trastuzumab through Fc gamma receptors (FcγRs) was tested using three trastuzumab variants with compromised or no Fc (fragment crystallizable) functions and FcγRs blocking experiments. The engagement of immune cells by trastuzumab in HER2 downregulation was also evaluated in in vivo mouse xenograft tumor models. RESULTS: HER2 downregulation of cancer cells by trastuzumab occurred only when trastuzumab was actively engaged with immune cells and cancer cells, as demonstrated consistently in co-cultures of cancer cell lines with PBMCs and in vivo mouse xenograft tumor models. We further demonstrated that HER2 downregulation in cancer cells by immune-cell-engaged trastuzumab was at the transcriptional level, not through the HER2 degradation pathway. Activation of signal transducer and activator of transcription 1 (STAT1) in cancer cells by the increased interferon gamma (IFN-γ) production in immune cells played an important role in downregulating HER2 in cancer cells upon engagement of immune cells by trastuzumab. Furthermore, HER2 downregulation in cancer cells induced by trastuzumab engagement of immune cells was correlated with the antibody’s antitumor efficacy in vivo. CONCLUSIONS: This study reveals that engagement of immune effector cells by trastuzumab induces HER2 downregulation in HER2-expressing cancer cells, which represents a new function of immune cells in trastuzumab-mediated antitumor efficacy and serves as a novel mechanism of action for trastuzumab. Our results imply that HER2 downregulation in cancer cells treated by trastuzumab may predict active engagement of immune effector cells in tumor microenvironment.